Quality of essential surgical care in low- and middle-income countries: a systematic review of the literature. (18th July 2018) - Saluja, Saurabh; Mukhopadhyay, Swagoto; Amundson, Julia R; Silverstein, Allison; Gelman, Jessica; Jenny, Hillary; Lin, Yihan; Moccia, Anthony; Rashad, Ramy; Sood, Rachita; Raykar, Nakul P; Shrime, Mark G
Abstract: Purpose: Quality of care is an emerging area of focus in the surgical disciplines. However, much of the emphasis on quality is limited to high-income countries. To address this gap, we conducted a systematic review of the literature on the quality of essential surgical care in low- and middle- income countries (LMIC). Data sources: We searched PubMed, Cinahl, Embase and CAB Abstracts using three domains: quality of care, surgery and LMIC. Study selection: We limited our review to studies of essential surgeries that pertained to all three search domains. Data extraction: We extracted data on study characteristics, type of surgery and the way in which quality was studied. Results of data synthesis: 354 studies were included. 281 (79.4%) were single-center studies and nearly half ( n = 169, 46.9%) did not specify the level of facility. 207 studies reported on mortality (58.47%) and 325 reported on a morbidity (91.81%), most commonly surgical site infection ( n = 190, 53.67%). Of the Institute of Medicine domains of quality, studies were most commonly of safety ( n = 310, 87.57%) and effectiveness ( n = 180, 50.85%) and least commonly of equity ( n = 21, 5.93%). Conclusion: We find that while there are numerous studies that report on some aspects of quality of care, much of the data is single center and observational. Additionally, there is variability on which outcomes are reported both within and across specialties. Finally, we find under-reporting of parameters of equity and timeliness, which may be critical areas for research moving forward.